PEMBUATAN MODEL ALAT UKUR BAHAN BAKAR TANGKI HELIKOPTER MENGGUNAKAN METODE KAPASITANSI - Adi Putra Toga Torop; Yohannes Dewanto; Bekti Yulianti (JURNAL TEKNOLOGI INDUSTRI, 2019)
Helicopters are heavier-than-air aircraft, with swivel wings with propellers, getting their spin from the transmission rotated by the engine. Helicopters are classified as rotary wing aircraft to distinguish them from aircraft with fixed wings. The fuel quantity in the instrument panel shows the amount of fuel as measured by the sensing unit in the tank. Most helicopter fuel measurements show in gallons (ponds), and will be accurate only when empty. So that the calibration is carried out when the fuel is fully filled and when the fuel is empty in the tank.In order to more easily understand the analysis of helicopter fuel using this capacitance method, a schematic diagram was designed. The measuring instrument was tested when submerged in water at a height of 5 cm, 10 cm, 15 cm, and 20 cm.Keyword : Helicopter, Capasitor, Ardunio, Sketch.